2012
DOI: 10.2139/ssrn.1987486
|View full text |Cite
|
Sign up to set email alerts
|

Fat-Tail Distributions and Business-Cycle Models

Abstract: Recent empirical findings suggest that macroeconomic variables are seldom normally distributed. For example, the distributions of aggregate output growth-rate time series of many OECD countries are well approximated by symmetric exponential-power (EP) densities, with Laplace fat tails. In this work, we assess whether Real Business Cycle (RBC) and standard medium-scale New-Keynesian (NK) models are able to replicate this statistical regularity. We simulate both models drawing Gaussian-vs Laplace-distributed sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
(14 reference statements)
1
9
0
Order By: Relevance
“…The departure of the distribution of aggregate economic variables from normality in the United States and other OECD economies has also been documented by several prior studies, including Lee et al (1998) ;Canning et al (1998); Christiano (2007) ;Fagiolo, Napoletano, and Roventini (2008) ;Cúrdia, Del Negro, and Greenwald (2014); and Ascari, Fagiolo, and Roventini (2015).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…The departure of the distribution of aggregate economic variables from normality in the United States and other OECD economies has also been documented by several prior studies, including Lee et al (1998) ;Canning et al (1998); Christiano (2007) ;Fagiolo, Napoletano, and Roventini (2008) ;Cúrdia, Del Negro, and Greenwald (2014); and Ascari, Fagiolo, and Roventini (2015).…”
mentioning
confidence: 54%
“…Our work is also related to Lee et al (1998);Canning et al (1998);Fagiolo, Napoletano, and Roventini (2008) ;Cúrdia, Del Negro, and Greenwald (2014);and Ascari, Fagiolo, and Roventini (2015), who document that the normal distribution does not provide a good approximation to many macroeconomic variables in OECD countries. Similarly, Atalay and Drautzburg (2015) find substantial cross-industry differences in the departures of employment growth rates from the normal distribution, and compute the contribution of the independent component of industry-specific productivity shocks to the skewness and kurtosis of aggregate variables.…”
mentioning
confidence: 99%
“…Moreover, we show the model is endogenously able to generate both mild and "deep" downturns. In that the K+S model appears to be more successful than its DSGE counterparts, which do not generate major crises even when they are fed with exogenous fat-tailed shocks (more on that in Ascari et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Acemoglu and Scott (1991) have demonstrated how the last two features, namely persistence and asymmetry, can be accounted by allowing heterogeneity among producers and some form of increasing returns at the firm level. Lastly, as Ascari et al (2015) have shown DSGE models cannot explain the observation that the tails of the distribution of aggregate shocks are 'fat'; that is are inconsistent with normal draws. This last observation has recently motivated researchers to consider alternative approaches, such as network theory (e.g.…”
Section: Future Challengesmentioning
confidence: 98%